Different dietary intake of carbohydrates in glycemic control in pregnant women with diabetes mellitus type 2: case report - admin, Investigación Materno Perinatal (2023)
Introduction. The glycemic impact of moderately high or low carbohydrate intake in an isocaloric diet remains undetermined. Report. An intervention was carried out with pregnant women with type 2 diabetes, who were fitted with a continuous glucose monitor for two weeks. They followed two 7-day nutritional plans, the first with 60% of the total caloric valuecoming from carbohydrates (VCT60), and the second with 40% of the total caloric value from carbohydrates (VCT40).On the first day of each week, a supervised breakfast corresponding to the intervention was provided. During the VCT60week, there was a tendency for: lower average glucose, higher number of hypoglycemia events, and higher frequency ofsensor scans compared to the VCT40 week. Conclusion. The continuous glucose monitor was well-received and assisted in making decisions regarding their diet and medical treatment.